(untitled) (Research, Society and Development, 2021)
The fear of feeling pain during dental treatments is one of the main reasons why society avoids undergoing them. The use of local anesthetics is necessary in most of these treatments and it is with the success of this technique that a good relationship between professional and patient begins. With the advancement of technology in the last decade, new techniques and alternative electronic devices have emerged in order to increase patient comfort during anesthetic administration. This paper seeks to report the benefits, advantages and disadvantages that electronic devices bring to the application of local anesthetics in dentistry, as well as their difference with the traditional manual anesthesiology technique through a literature review. This is a literature review, in which searches will be performed in worldwide bibliographic databases such as: Pubmed, Scielo, Lilacs and Cochrane. Articles and works published between 2010 and 2020, written in English, Portuguese and Dutch, will be selected. As a result, the use of electronic devices in dental anesthesiology is a great advance for dentistry worldwide. This modernization aims to facilitate and improve the relationship between surgeon-dentists and patients, providing greater comfort during appointments that require the use of anesthesia.